(untitled) (Research, Society and Development, 2021)
The state of Mato Grosso occupies an important position in the national production of corn and, due to the climatic conditions, the drying of the grains, in most of the state, happens naturally in the field, which can imply in qualitative and quantitative losses resulting, for example, from excessive drying. Thus, the present study aimed to evaluate: the natural drying kinetics and the effect on physical properties and physiological quality of corn grains. Four hybrids were evaluated: RB9110PRO2, 2B512PW, 2B633PW and 2A401PW. Harvesting started after physiological maturity. The initial water content ranged from 25 to 32% (w.b.) and the harvests were performed periodically until a water content close to the storage level of 13% (w.b.) was obtained. The natural drying kinetics was evaluated by the rate of reduction of the product’s water content while remaining in the field. The physical and physiological quality of the grains was evaluated by thousand-grain mass, bulk density and true density and size and shape of the grains, and by the germination and accelerated aging tests. The quadratic polynomial model describes well the variation of the water content during the natural drying. With the reduction of the water content there was an increase in the apparent and unit specific mass and a decrease in the mass of one thousand grains and in the size and shape of the grains. The physiological quality does not vary due to natural drying in the field.